Attitudes Toward Transgender Persons Among Medical Students of a Tertiary Health-Care Center: A Cross-Sectional Exploratory Study. Issue 3 (July 2022) - Jain, Harsh; Subramanian, Karthick; Gowsi, Keni; Sankaran, Avudaiappan
Background: Inadequate knowledge and awareness about transgenderism among doctors can lead to inadequate health-care services to transgender persons. Objective: To assess the prevalent attitudes and beliefs toward transgender persons amongst medical undergraduates. Materials and Methods: The present cross-sectional observational study included medical undergraduates of both gender in a tertiary care hospital. The students belonged to "early clinical phase" (yet to start clinical postings). The sociodemographic characteristics and academic and social exposure to transgender-related issues were recorded using a semi-structured proforma. Transgender Attitudes and Beliefs Scale was used to assess the attitudes and beliefs toward transgender persons. Statistical significance was set at P < .05. Results: Of the 170 second-year medical students, majority reported negligible social exposure (71.3%) and academic exposure (81.6%) to transgenderism. Female students displayed better attitudes and beliefs toward transgender persons than their male counterparts. Conclusions: Medical undergraduates require systematic academic exposure to transgender-related health issues. Gender differences exist among medical undergraduates in the beliefs and attitudes toward transgenderism.